RNA-binding proteins regulate post-transcriptional responses to TGF-β to coordinate function and mesenchymal activation of murine endothelial cells - Wardman, Rhys; Keles, Merve; Pachkiv, Ihor; Hemanna, Shruthi; Grein, Steve; Schwarz, Jennifer; Stein, Frank; Ola, Roxana; Dobreva, Gergana; Hentze, Matthias W.; Heineke, Jörg (Arteriosclerosis, thrombosis, and vascular biology, 2023)
BACKGROUND: - - Endothelial cells (ECs) are primed to respond to various signaling cues. For example, TGF (transforming growth factor)-β has major effects on EC function and phenotype by driving ECs towards a more mesenchymal state (ie, triggering endothelial to mesenchymal activation), a dynamic process associated with cardiovascular diseases. Although transcriptional regulation triggered by TGF-β in ECs is well characterized, post-transcriptional regulatory mechanisms induced by TGF-β remain largely unknown. - - METHODS: - - Using RNA interactome capture, we identified global TGF-β driven changes in RNA-binding proteins in ECs. We investigated specific changes in the RNA-binding patterns of hnRNP H1 (heterogeneous nuclear ribonucleoprotein H1) and Csde1 (cold shock domain containing E1) using RNA immunoprecipitation and overlapped this with RNA-sequencing data after knockdown of either protein for functional insight. Using a modified proximity ligation assay, we visualized the specific interactions between hnRNP H1 and Csde1 and target RNAs in situ both in vitro and in mouse heart sections. - - RESULTS: - - Characterization of TGF-β-regulated RBPs (RNA-binding proteins) revealed hnRNP H1 and Csde1 as key regulators of the cellular response to TGF-β at the post-transcriptional level, with loss of either protein-promoting mesenchymal activation in ECs. We found that TGF-β drives an increase in binding of hnRNP H1 to its target RNAs, offsetting mesenchymal activation, but a decrease in Csde1 RNA-binding, facilitating this process. Both, hnRNP H1 and Csde1, dynamically bind and regulate specific subsets of mRNAs related to mesenchymal activation and endothelial function. - - CONCLUSIONS: - - Together, we show that RBPs play a key role in the endothelial response to TGF-β stimulation at the post-transcriptional level and that the RBPs hnRNP H1 and Csde1 serve to maintain EC function and counteract mesenchymal activation. We propose that TGF-β profoundly modifies RNA-protein interaction entailing feedback and feed-forward control at the post-transcriptional level, to fine-tune mesenchymal activation in ECs.
Gesehen am 27.11.2023